Mechanisms underlying acquired platinum resistance in high grade serous ovarian cancer - a mini review - Binju, Mudra; Padilla, Monica Amaya; Singomat, Terence; Kaur, Pritinder; Suryo Rahmanto, Yohan; Cohen, Paul A.; Yu, Yu (Biochimica et biophysica acta. General subjects, 2019)
Advanced epithelial ovarian cancer is one of the hardest human malignancies to treat. Standard treatment involves cytoreductive surgery and platinum-based chemotherapy, however, median progression-free survival for patients diagnosed with advanced stage disease (FIGO stages III and IV) is approximately 18 months. There has been little improvement in overall survival over the past decade and less than half of women with advanced stage disease will be living 5 years after diagnosis. A majority of patients initially have a favourable response to platinum-based chemotherapy, but most will eventually relapse and their disease will become platinum resistant. Here, we review our current understanding of mechanisms that promote recurrence and acquired resistance in epithelial ovarian cancer with particular focus on studies that describe differences observed between untreated primary tumors and recurrent tumors, post-first-line chemotherapy. Multiple molecular mechanisms contribute to recurrence in patients following initial treatment for advanced epithelial ovarian cancer including those involving the tumor microenvironment, tumor immune status, cancer stem cells, DNA repair/cell survival pathways and extracellular matrix. Due to the adaptive nature of recurrent tumors, the major contributing and specific resistance pattern may largely depend on the nature of the primary tumor itself. Future work that aims to elucidate the complex pattern of acquired resistance will be useful for predicting chemotherapy response/recurrence following primary diagnosis and to develop novel treatment strategies to improve the survival of patients with advanced epithelial ovarian cancer, especially in tumors not harbouring homologous DNA recombination repair deficiencies. •Advanced epithelial ovarian cancer has high relapse.•The major drug resistant pattern may depend on the primary tumor itself.•Tumor recurrence mechanisms involve the microenvironment, immune status, cancer stem cells, DNA repair/cell survival pathways and extracellular matrix.